Second St. Gallen European Organisation for Research and Treatment of Cancer Gastrointestinal Cancer Conference: consensus recommendations on controversial issues in the primary treatment of rectal cancer - Lutz, MP (2016)
Primary treatment of rectal cancer was the focus of the second St. Gallen European Organisation for Research and Treatment of Cancer (EORTC) Gastrointestinal Cancer Conference. In the context of the conference, a multidisciplinary international expert panel discussed and voted on controversial issues which could not be easily answered using published evidence. Main topics included optimal pretherapeutic imaging, indication and type of neoadjuvant treatment, and the treatment strategies in advanced tumours. Here we report the key recommendations and summarise the related evidence. The treatment strategy for localised rectal cancer varies from local excision in early tumours to neoadjuvant radiochemotherapy (RCT) in combination with extended surgery in locally advanced disease. Optimal pretherapeutic staging is a key to any treatment decision. The panel recommended magnetic resonance imaging (MRI) or MRI + endoscopic ultrasonography (EUS) as mandatory staging modalities, except for early T1 cancers with an option for local excision, where EUS in addition to MRI was considered to be most important because of its superior near-field resolution. Primary surgery with total mesorectal excision was recommended by most panellists for some early tumours with limited risk of recurrence (i.e. cT1-2 or cT3a N0 with clear mesorectal fascia on MRI and clearly above the levator muscles), whereas all other stages were considered for multimodal treatment. The consensus panel recommended long-course RCT over short-course radiotherapy for most clinical situations where neoadjuvant treatment is indicated, with the exception of T3a/b N0 tumours where short-course radiotherapy or even no neoadjuvant therapy were regarded to be an option. In patients with potentially resectable tumours and synchronous liver metastases, most panel members did not see an indication to start with classical fluoropyrimidine-based RCT but rather favoured preoperative short-course radiotherapy with systemic combination chemotherapy or alternatively a liver-first resection approach in resectable metastases, which both allow optimal systemic therapy for the metastatic disease. In general, proper patient selection and discussion in an experienced multidisciplinary team was considered as crucial component of care.